The role of ADAR1 in human pathophysiology - Li, Jiahao; Xiao, Yushan; Li, Xiaofeng; Dai, Yan (Frontiers in Cell and Developmental Biology, 2025)
Adenosine deaminase 1 (ADAR1) is an enzyme acting on double-stranded RNA, primarily responsible for catalyzing the adenosine-inosine deamination reaction of dsRNA.An increasing number of studies have demonstrated that ADAR1 plays a pivotal role in various diseases, including cardiovascular, neurological, and immune disorders, among others. Some of these diseases remain incurable. In addition, ADAR1 is also involved in the development and differentiation of various crucial cells, such as hematopoietic stem cells and nerve cells. This article comprehensively summarizes the regulatory effects of ADAR1 on crucial cells and organs across the immune, nervous, respiratory, blood, and digestive systems, along with its influence on disease progression. The aim is to offer assistance in intervening in cells and treating diseases.